2018
DOI: 10.1017/s1478951518000536
|View full text |Cite
|
Sign up to set email alerts
|

Liminality as a dimension of the experience of living with terminal cancer

Abstract: The analysis forms part of a wider project that involved conducting a metasynthesis of 23 phenomenological studies of the experience of living with the awareness of having terminal cancer published between 2011 and 2016.ResultThe metasynthesis identified four master themes that represent distinct experiential dimensions of living with terminal cancer. This paper focuses on one of these themes, liminality, to provide novel insights into the structure of death awareness whilst living with terminal cancer.Signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…And when experiencing either ambiguous symptoms or known side-effects of therapy, patients might also feel insecure or at risk of relapse. These findings are consistent with other research on cancer-related uncertainty in patients and even with research in patients with other diseases, such as HIV (Brashers, Neidig, Reynolds, & Haas, 1998; Liao, Chen, Chen, & Chen, 2008; Nelson, 1996; Pietilä, Jurva, Ojala, & Tammela, 2018; Willig & Wirth, 2019). Feelings of liminality pre-diagnosis have not received much attention in the literature (Granek & Fergus, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…And when experiencing either ambiguous symptoms or known side-effects of therapy, patients might also feel insecure or at risk of relapse. These findings are consistent with other research on cancer-related uncertainty in patients and even with research in patients with other diseases, such as HIV (Brashers, Neidig, Reynolds, & Haas, 1998; Liao, Chen, Chen, & Chen, 2008; Nelson, 1996; Pietilä, Jurva, Ojala, & Tammela, 2018; Willig & Wirth, 2019). Feelings of liminality pre-diagnosis have not received much attention in the literature (Granek & Fergus, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…This mainly is due to space restrictions but also reflects the meta-synthesis' primary function, which is to map out the experiential spaces available to people living with terminal cancer and to identify their defining features. Separate papers on each of the four master themes will be published, which will give voice to participants and explore the tensions and contextual dimensions of the themes in more detail (e.g., Willig & Wirth, 2017).…”
Section: Reflections On the Use Of Meta-synthesis Methodologymentioning
confidence: 99%
“…Several explorations of liminality [42][43][44][45][46] identify a liminal space as a time of waiting for what will come next, be that test results, future treatment, or death itself; the participants in my study found such things psychologically challenging as well. Adorno 45 states that liminality is increased by the advent of biomedical technologies, which cause a greater blurring between living and dying.…”
Section: Liminalitymentioning
confidence: 99%